2013
DOI: 10.3390/ijms140715029
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Cancer Diagnosis

Abstract: DNA methylation is a major epigenetic modification that is strongly involved in the physiological control of genome expression. DNA methylation patterns are largely modified in cancer cells and can therefore be used to distinguish cancer cells from normal tissues. This review describes the main technologies available for the detection and the discovery of aberrantly methylated DNA patterns. It also presents the different sources of biological samples suitable for DNA methylation studies. We discuss the interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 150 publications
(170 reference statements)
2
90
0
5
Order By: Relevance
“…for the establishment of DNA methylation patterns during development [12][13]. In this study we demonstrated that DNMTI procaine inhibited DNMT1 gene expression after 24 h of treatment.…”
Section: Procaine Induced Epigenetic Changes Mediated By Histone H3 Mmentioning
confidence: 70%
See 1 more Smart Citation
“…for the establishment of DNA methylation patterns during development [12][13]. In this study we demonstrated that DNMTI procaine inhibited DNMT1 gene expression after 24 h of treatment.…”
Section: Procaine Induced Epigenetic Changes Mediated By Histone H3 Mmentioning
confidence: 70%
“…DNMT1 is known as maintenance DNMT which is responsible for the exact copying of the DNA methylation pattern on the neo-synthesized strand during DNA replication. DNMT1 expression is tightly regulated during the cell cycle by several mechanisms and maximal expression occurs during S phase [12][13]. The de novo DNA methyltransferases DNMT3a and DNMT3b are responsible Fig.4.…”
Section: Discussionmentioning
confidence: 99%
“…DNMT1 plays prominent and pertinent role for DNA methylation during DNA replication. DNMT1 over expression was reported in lung, colorectal, prostate, breast, gastric and oral cavity cancers (Delpu et al, 2013). It has been pointed out that DNMT inhibition might lead to reactivation of the silenced genes.…”
Section: Discussionmentioning
confidence: 99%
“…Since aberrant expression of DNMT1 occurs in the majority of cancer types, DNA methylation-based biomarkers mediated by DNMT1 have been used as diagnostic tools, with modification typically occurring in the CpG-rich island of the gene promoter region (19)(20)(21). Therefore, it has been suggested that DNA methylation patterns may be used to distinguish cancer cells from normal cells (22).…”
Section: Discussionmentioning
confidence: 99%